Graphene-based nanolaminates as ultra-high permeation barriers - Sagade, Abhay A.; Aria, Adrianus Indrat; Edge, Steven; Melgari, Paolo; Gieseking, Bjoern; Bayer, Bernhard C.; Meyer, Jannik C.; Bird, David; Brewer, Paul; Hofmann, Stephan (Nature Publishing Group, 2017)
Permeation barrier films are critical to a wide range of applications. In particular, for organic electronics and photovoltaics not only ultra-low permeation values are required but also optical transparency. A laminate structure thereby allows synergistic effects between different materials. Here, we report on a combination of chemical vapor deposition (CVD) and atomic layer deposition (ALD) to create in scalable fashion few-layer graphene/aluminium oxide-based nanolaminates. The resulting ~10 nm contiguous, flexible graphene-based films are >90% optically transparent and show water vapor transmission rates below 7 × 10−3 g/m2/day measured over areas of 5 × 5 cm2. We deploy these films to provide effective encapsulation for organic light-emitting diodes (OLEDs) with measured half-life times of 880 h in ambient.
Keywords: Electronic devices; Mechanical and structural properties and devices